The Comparison of Metronidazole, Clindamycin, and Amoxicillin Againts Streptococcus sanguinis - Kevin Lim; Armelia Sari Widyarman (Journal of Indonesian Dental Association, 2018)
Introduction: Viridans streptococci group such as Streptococcus sanguinis (S. sanguinis), an anaerobic Gram-positive bacteria is a well-known for its involvement in dry socket (alveolar osteitis)-associated infection. Systemic amoxicillin, clindamycin and metronidazole have all been shown to be effective to inhibit this bacterium. However, there has been a lack of studies identifying which are the most effective amongst these antibiotics toward Streptococcus sanguinis. Objectives: The purpose of this study is to evaluate the effectiveness of metronidazole, clindamycin, and amoxicillin in inhibiting the growth of Streptococcus sanguinis in vitro. Methods: This effectiveness was done by using agar well diffusion methods. S. sanguinis ATCC 10556 were cultured in Brain Heart Infusion (BHI) broth at 37°C under anaerobic condition. After 48h, bacterial cells were harvested and counted using microplate reader (490 nm) to achieve optical density of 0.25-0.30 (107 CFU/mL). Subsequently, 100 μL of bacterial suspension was cultured on BHI agar and each antibiotic suspension was added into each agar well, incubated for 72h at 37°C. The inhibition zone diameters were measured with electronic caliper. All experiments were done in triplicate, and repeated two times in separated occasions. The obtained data were statistically analyzed using one-way ANOVA test. A p<0.05 was considered as significance. Result: The results showed that there was a significant difference in the effectiveness, clindamycin and amoxicillin in inhibiting the growth of Streptococcus sanguinis (p<0.05), compared to metronidazole. The inhibition zone diameter with mean±SD (mm) are 13.50±2.0, 34.67±2.3 and 32.67±1.7 for metronidazole, clindamycin and amoxicillin, respectively. Conclusion: Clindamycin and amoxicillin are more effective in inhibiting the growth of Streptococcus sanguinis compared to metronidazole in this study. However, future studies are needed to confirm this result in vivo.